2010
DOI: 10.4028/www.scientific.net/kem.459.194
|View full text |Cite
|
Sign up to set email alerts
|

A Design Method for Two-Degree-of-Freedom Multi-Period Repetitive Control Systems

Abstract: Multi-period repetitive controllers improve the disturbance attenuation characteristic of the modified repetitive control system that follows the periodic reference input with a small steady state error. Recently, the parameterization of all stabilizing multi-period repetitive controllers was studied. However, when the parameterization of all stabilizing multi-period repetitive controllers is used, the input-output characteristic and the feedback characteristic cannot be specified separately. From the practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Obviously, Figure 3 illustrates that ( ) ∈ ∞ . This demonstrates that the design method for the free parameters̃( ) and 0 ( ) is much more effective than that in [12,13].…”
Section: Numerical Examplesmentioning
confidence: 92%
See 3 more Smart Citations
“…Obviously, Figure 3 illustrates that ( ) ∈ ∞ . This demonstrates that the design method for the free parameters̃( ) and 0 ( ) is much more effective than that in [12,13].…”
Section: Numerical Examplesmentioning
confidence: 92%
“…For multiple-period systems that have a similar structure to the high-order repetitive control system, solutions are given by Yamada et al [12] and Yamada et al [13] using the Youla-Kucera parametrization (YKP) without solving the problem of designing the free parameters.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Some related literature on multidegree-of-freedom coupling dynamic model have been published recently. Sakanushi et al [17] and Yamada et al [18] proposed the control characteristics and a design procedure of a two-degree-of-freedom simple repetitive control system which can specify the input-output characteristic and the disturbance attenuation characteristic separately, and a numerical example and an application in motors were presented to illustrate the effectiveness, which showed that the control system was expected to be used in practical applications. A six-degree-of-freedom fully-coupled plant model used in underwater vehicles was reported in [19], and the comparative experimental evaluations were estimated experimentally from data obtained in free-motion vehicle trials, which might be able to predict the performance of underwater vehicles.…”
Section: Introductionmentioning
confidence: 99%